Collision of viscoelastic spheres: Compact expressions for the coefficient of normal restitution - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The coefficient of restitution of colliding viscoelastic spheres is known analytically as a complete series expansion in terms of the impact velocity where all (infinitely many) coefficients are known. While being analytically exact, this result is not suitable for applications in efficient event-driven molecular dynamics (eMD) or direct simulation Monte Carlo (DSMC) methods. Based on the analytic result, here we derive expressions for the coefficient of restitution that allow for application in efficient eMD and DSMC simulations of granular systems. © 2011 American Physical Society.